Effect of waxy rice starch on textural and microstructural properties of microwave‐puffed cheese chips. (9th July 2017) - Liu, Lu; Zhang, Hua; Li, Xiaodong; Han, Xiue; Qu, Xiuwei; Chen, Ping; Wang, Haixia; Wang, Lina
Abstract : Protein‐based expanded snacks sometimes do not have homogeneous structures. However, starches are widely used in expanded food snacks because of their good puffing characteristics. We aimed to use waxy rice starch to partially substitute for sodium caseinate in caseinate‐based and caseinate plus soya protein (double‐protein) microwave‐puffed imitation cheese snacks to improve their textural, microstructural and sensory properties. The single‐protein chips without waxy rice starch and the double‐protein chips with a low degree of expansion were not well appreciated, whereas the chips with up to 8 g of waxy rice starch per 100 g of product were scored highly by the panellists. Our results demonstrated that waxy rice starch can improve the expansion, homogeneity, hardness, crispness and colour of imitation cheeses.